The Development Of Teaching Materials With Problem Based Learning On The Mathematical Statistics Subject To Improve Students Critical Thinking Ability - Irvan Irvan; Rahmat Muslihuddin (Indonesian Journal of Education and Mathematical Science, 2021)
The existence of teaching materials has an important role in the learning process. One way to improve the quality of learning is by providing teaching materials (LKM) based on needs. Teaching materials used in this study are the student worksheets based on problems in mathematics statistics courses. The purpose of this study is to develop, test and determine the effectiveness of problem-based teaching materials (LKM). This study applies qualitative and quantitative descriptive data analysis and percentage techniques. The result of this study obtained: Problem-based teaching materials (LKM) that use critical thinking skills indicators; the feasibility of problem-based teaching materials (LKM) according to the lecturers or friends, with an average of 88.69% (good), while according to the students it obtained an average of 81.26% (good). Teaching Materials (LKM) for Mathematical Statistics based on effective problems improve critical thinking skills with a gain of 14.17 and N-gain 0.38 in the medium category.